Opium use and risk of bladder cancer: a multi-centre case-referent study in Iran. (4th March 2022) - Hadji, Maryam; Rashidian, Hamideh; Marzban, Maryam; Naghibzadeh-Tahami, Ahmad; Gholipour, Mahin; Mohebbi, Elham; Safari-Faramani, Roya; Seyyedsalehi, Monireh Sadat; Hosseini, Bayan; Bakhshi, Mahdieh; Alizadeh-Navaei, Reza; Ahmadi, Lida; et al.
Abstract: Background: Bladder cancer (BC) is the 10th most common type of cancer worldwide and the fourth most common type of cancer in Iran. Opium use is considered as one of the risk factors for BC. We aim to assess the association between various parameters of opium use, which in Iran is mainly ingested or smoked in various forms, and the risk of BC. Method: In this multi-centre case-referent study in Iran, 717 BC cases and 3477 referents were recruited to the study from May 2017 until July 2020. Detailed histories of opium use (duration, amount, frequency) and potential confounders were collected by trained interviewers. Multivariable unconditional logistic regression models were used to measure adjusted odds ratio (OR) and 95% confidence intervals (CI). The ORs were adjusted for age, gender, place of residence and pack-years of cigarette smoking. Results: Regular opium consumption was associated with an increased risk of BC (OR 3.5, 95% CI: 2.8, 4.3) compared with subjects who never used opium. Compared with continuous users, the risk decreased to one-third for those who stopped opium more than 10 years ago. The adjusted OR for those who used both crude opium (teriak) and opium juice was 7.4 (95% CI: 4.1, 13.3). There was a joint effect of opium and tobacco (OR for users of both opium and tobacco 7.7, 95% CI: 6.0, 9.7). Conclusions: Regular opium use is associated with an approximately 4-fold risk for BC. The OR decreases along with the increasing time since stopping opium use.